2010
DOI: 10.1099/mic.0.038380-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptome analyses of the ‘Knallgas’ bacterium Ralstonia eutropha H16 with regard to polyhydroxyalkanoate metabolism

Abstract: Ralstonia eutropha H16 is probably the best-studied 'Knallgas' bacterium and producer of poly(3-hydroxybutyrate) (PHB). Genome-wide transcriptome analyses were employed to detect genes that are differentially transcribed during PHB biosynthesis. For this purpose, four transcriptomes from different growth phases of the wild-type H16 and of the two PHB-negative mutants PHB " 4 and DphaC1 were compared: (i) cells from the exponential growth phase with cells that were in transition to stationary growth phase, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 68 publications
5
86
0
1
Order By: Relevance
“…We also examined genes involved in the glyoxylate bypass of R. eutropha H16 and their roles in oil and fatty acid utilization. Comparison of gene expression under growth and PHB production conditions confirms results from previous studies by our group and others (24,37,39,44,46,(62)(63)(64)(65). In addition, we determined that deletion of fatty acid metabolism and glyoxylate bypass genes does not affect PHB production or utilization in R. eutropha.…”
supporting
confidence: 77%
“…We also examined genes involved in the glyoxylate bypass of R. eutropha H16 and their roles in oil and fatty acid utilization. Comparison of gene expression under growth and PHB production conditions confirms results from previous studies by our group and others (24,37,39,44,46,(62)(63)(64)(65). In addition, we determined that deletion of fatty acid metabolism and glyoxylate bypass genes does not affect PHB production or utilization in R. eutropha.…”
supporting
confidence: 77%
“…2B). A previous analysis suggested that PhaC2 could compensate for the mutation in PhaC1 in the chemically induced PHB-negative mutant R. eutropha PHB-4 (29). However, when we transferred phaC2-eyfp (with the constitutive phaC1 promoter) to R. eutropha PHB-4, we did not find evidence for PHB granule formation under culture conditions permissive for PHB accumulation (data not shown).…”
Section: Resultsmentioning
confidence: 46%
“…This observation, combined with the low levels of phaB2 expression measured in fructose and trioleate cultures ( Table 2), suggests that this gene is not expressed under normal laboratory conditions. Another group similarly concluded that the phaC2 gene, which is immediately downstream of phaB2 in the R. eutropha genome, is unexpressed (27).…”
Section: Discussionmentioning
confidence: 99%